2006
DOI: 10.1080/09513590601015051
|View full text |Cite
|
Sign up to set email alerts
|

Difficult management of recurrent catamenial pneumothorax

Abstract: Catamenial pneumothorax is an uncommon disease whose management is not consensual. We report the case of a patient who experienced several episodes of pneumothorax. She was initially treated by repair of diaphragmatic defects and hormonal treatment. During the therapeutic amenorrhea, no recurrence occurred. However, each cessation of medical therapy was followed by recurrence. Finally, talc pleurodesis and tubal ligature were performed without any recurrence in the subsequent 12 months. This report outlines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…For patients with endometriosis, it should prevent recurrence originating from microscopic endometrial foci or from newly implanted lesions. We previously recommended careful pleural abrasion (6), and suggested that pleurectomy or talc pleurodesis should be considered in the case of treatment failure (15,16). Despite surgery and prolonged hormonal therapy, we observed a high recurrence rate: 14% of the entire population, 32% of patients with CP, and 27% of patients with endometriosis-related non-CP.…”
Section: Discussionmentioning
confidence: 85%
“…For patients with endometriosis, it should prevent recurrence originating from microscopic endometrial foci or from newly implanted lesions. We previously recommended careful pleural abrasion (6), and suggested that pleurectomy or talc pleurodesis should be considered in the case of treatment failure (15,16). Despite surgery and prolonged hormonal therapy, we observed a high recurrence rate: 14% of the entire population, 32% of patients with CP, and 27% of patients with endometriosis-related non-CP.…”
Section: Discussionmentioning
confidence: 85%
“…Four cases reported a right-sided pneumothorax (80%) that seems to be the most frequent side for location of thoracic endometriosis, while in one case (20%) pneumothorax has not been reported but thoracic endometriosis syndrome was associated with the presence of right-sided pleural effusion and adhesions on the pleural surface with hemorrhagic spots 57 . The thoracic location of endometriosis was associated with an intestinal endometriosis in 20% of the cases 56 , while in another case the patient presented also adenomyosis, ovarian cyst, and ascites 57 . Clinically, chest pain during menstrual period was present in four cases (80%) and other respiratory symptoms, such as breathlessness, cough, and chest discomfort, have also been frequently reported in association (60%).…”
Section: Management Of Rare Endometriosis: Thoracic Endometriosis Syn...mentioning
confidence: 93%
“…Consistent data on the management of thoracic endometriosis syndrome in the perimenopause period are lacking; five cases of thoracic endometriosis in women aged 40-50 years have been described 51,56,57 . Four cases reported a right-sided pneumothorax (80%) that seems to be the most frequent side for location of thoracic endometriosis, while in one case (20%) pneumothorax has not been reported but thoracic endometriosis syndrome was associated with the presence of right-sided pleural effusion and adhesions on the pleural surface with hemorrhagic spots 57 .…”
Section: Management Of Rare Endometriosis: Thoracic Endometriosis Syn...mentioning
confidence: 99%